Modal Sosial Dalam Pemenangan Calon Kepala Desa - Aditya, I Gede Restu; Ali Azhar, Muh.; Pramana, Gede Indra (Jurnal Nawala Politika, 2021)
The0purpose0of0this study0is to determine the use of0social capital for I Gede Marjaya's victory in the 2019 Tista Village Head Election. The theory used in this study refers to the thoughts of a philosophical expert, Pierre Bourdieu in his understanding of Habitus, Ranah, and the concept of Social Capital. This0research0method0uses0a qualitative0descriptive0method.. Social capital contains three important elements, such as: trust, reciprocity and shared values.. The realm in this case is the place for the social capital of the actors to be staked and the formation of the actor's habitus in Tista Village through social interactions. Actors who compete in the political arena are equipped with support from social organizations and the ability to adapt to society in the struggle for positions as people's representatives. Keywords: Legislative Election, Habitus, Domain, Social Capital